2008
DOI: 10.1007/s10517-008-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxidized fibrinogen and hemostasis disturbances and endothelial dysfunction in myocardial infarction

Abstract: Oxidative modification of fibrinogen in acute myocardial infarction increased 1.3-fold compared to that in CHD and 1.5-fold surpassed that in the control without CHD. Elevated content of oxidized fibrinogen correlated with increased levels of LPO products, von Willebrand factor, and fibrin degradation products, with accelerated leukocyte and platelet aggregation, and reduced content of NO metabolites in the plasma. Independent associations of oxidized fibrinogen with myocardial infarction and typical thromboge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, the increased levels of plasma fibrinogen were implied not only with the long-term disorder of glycolipid metabolism but also with long time standing of low-grade systematic inflammatory reaction and atherosclerotic plaques progress in these settings [ 10 , 41 ]. In addition, impaired fibrinolysis or oxidative fibrinogen may exacerbate preexisting CAD and potentiate its evolution [ 9 ]. Besides, the formation of thrombi at the site of atherosclerotic lesions plays a central role in atherothrombosis, plaque evolution, and various acute cardiac events [ 3 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increased levels of plasma fibrinogen were implied not only with the long-term disorder of glycolipid metabolism but also with long time standing of low-grade systematic inflammatory reaction and atherosclerotic plaques progress in these settings [ 10 , 41 ]. In addition, impaired fibrinolysis or oxidative fibrinogen may exacerbate preexisting CAD and potentiate its evolution [ 9 ]. Besides, the formation of thrombi at the site of atherosclerotic lesions plays a central role in atherothrombosis, plaque evolution, and various acute cardiac events [ 3 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, few of them confirmed a correlation of high circulating plasma fibrinogen with adverse outcome in patients with CAD [ 1 , 4 , 6 ]. Meanwhile, recent observations indicated a relationship between fibrinogen and atherosclerotic plaque progress in patients with acute coronary syndrome (ACS) and stable CAD [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, with obesity-related oxidative stress, different biomolecules, including lipids, can be damaged [69]. LDL and proteins (e.g., fibrinogen) are modified to oxidized particles, which provoke all stages of the atherosclerosis process, starting with endothelial dysfunction, leukocyte activation, foam cell formation, and smooth muscle cell migration and proliferation, thus resulting in platelet adhesion and aggregation [70,71]. Oxidized LDL was also shown to be associated with the incidence of MS [72,73], which reflects the complex interlinkage of the described processes in their effects on CVD development.…”
Section: Cardiometabolic Conditionsmentioning
confidence: 99%
“…Thus, it is necessary to determine if some other risk factors may contribute to the formation and progression of CAD. Several studies have shown that fibrinogen is related to increased cardiovascular (CV) risk 12 and plaque progression in patients with acute coronary syndrome and stable angina [13][14][15] . The AtheroGene study 16 investigated 1806 patients with documented CAD and stable angina pectoris concluded that high fibrinogen and C reactive protein (CRP) values were predictive for future CV risk, but did not provide additional information on top of traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%